INVOLVEMENT OF CATALASE IN SACCHAROMYCES CEREVISIAE HORMETIC RESPONSE TO HYDROGEN PEROXIDE - Ruslana Vasylkovska; Nadia Burdylyuk; Halyna Semchyshyn (Vasyl Stefanyk Precarpathian National University, 2015)
In this study, we investigated the relationship between catalase activity and H2O2-induced hormetic response in budding yeast S. cerevisiae. In general, our data suggest that: (i) hydrogen peroxide induces hormesis in a concentration- and time-dependent manner; and (ii) the effect of hydrogen peroxide on yeast colony growth positively correlates with the activity of catalase that suggests the enzyme involvement in overall H2O2-induced stress response and hormetic response in yeast.